Helminths of lizards from the municipality of Aripuanã in the southern Amazon region of Brazil - Ávila, R. W.; Da Silva, R. J. [UNESP] (Cambridge University Press (CUP), 2013)
Ninety-five specimens from 13 species of lizard collected during a herpetofaunal monitoring programme of the Faxinal II power plant, municipality of Aripuanã, state of Mato Grosso, Brazil (southern Amazon region) were examined for helminths. A total of 21 helminth species (16 Nematoda, 1 Cestoda and 4 Trematoda) were recovered, with an overall prevalence of 67.37%. Seventeen new host records and seven new locality records are reported. A low number of specialists and core helminth species were found. Lizard body size was positively correlated with both the total number of helminth species and individuals. Active foragers exhibited higher helminth diversity. However, sit-and-wait foragers, especially Plica plica, had similar diversity values as active foragers and harboured more helminth species. The degree of similarity in helminth fauna was higher among closely related host species. Copyright © 2011 Cambridge University Press.
Keywords: animal experiment; body size; Brazil; cestode; fauna; foraging; Gekkonidae; Gymnophthalmidae; helminth; Hoplocercidae; Iguanidae; lizard; nematode; nonhuman; Phyllodactylidae; Plica plica; Polychrotidae; prevalence; species diversity; Sphaerodactylidae; Teiidae; trematode; Tropiduridae